Developing the CGIAR gender research agenda: Meeting slides - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
These slides were prepared and drafted during the CGIAR GENDER Platform's virtual workshop on July 13, 14 & 16, 2020.